2003
DOI: 10.1016/s0886-3350(03)00123-8
|View full text |Cite
|
Sign up to set email alerts
|

Corneal thickness measurements: Scanning-slit corneal topography and noncontact specular microscopy versus ultrasonic pachymetry

Abstract: Corneal thickness readings were comparable between scanning-slit topography and pachymetry; noncontact specular microscopy gave significantly smaller values. The measurements of the 3 methods showed significant linear correlations with one another. All methods provided acceptable repeatability of measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
98
7
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(116 citation statements)
references
References 17 publications
7
98
7
4
Order By: Relevance
“…Al-Ageel and Al Muammar reported that CCT was significantly thinner when measured with specular microscope (SM) (511.9 ± 38.6) (SP-2000P, Topcon Corporation, Tokyo, Japan) than when measured with UP (533.3 ± 37.9) (SP-3000, Tomey Corporation, Nagoya, Japan) and that the two instruments were in good correlation while measuring 94 normal eyes of 47 patients, with a mean age of 33 years (12) . In a multicenter study in Japan, both Orbscan and UP measurements were significantly higher than NSCM (SP-2000P, Topcon Corporation, Tokyo, Japan) measurements and ultrasonic pachymetry correlated with NCSM (13) . In contrast, Khaja et al reported lower values when comparing measurements made by UP vs. SM.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Al-Ageel and Al Muammar reported that CCT was significantly thinner when measured with specular microscope (SM) (511.9 ± 38.6) (SP-2000P, Topcon Corporation, Tokyo, Japan) than when measured with UP (533.3 ± 37.9) (SP-3000, Tomey Corporation, Nagoya, Japan) and that the two instruments were in good correlation while measuring 94 normal eyes of 47 patients, with a mean age of 33 years (12) . In a multicenter study in Japan, both Orbscan and UP measurements were significantly higher than NSCM (SP-2000P, Topcon Corporation, Tokyo, Japan) measurements and ultrasonic pachymetry correlated with NCSM (13) . In contrast, Khaja et al reported lower values when comparing measurements made by UP vs. SM.…”
Section: Discussionmentioning
confidence: 87%
“…Most of these studies reported that UP measurements were thicker than NCSM mea surements (10)(11)(12)(13) . Modis et al examined 73 eyes from 44 patients (mean age 66 years) with normal corneas comparing three different devices: NCSM (Topcon SP-2000P; Topcon Corporation, Tokyo, Japan), UP (AL-1000; Tomey, Erlangen, Germany), and contact specular microscope (CSM) (EM-1000; Tomey, Tokyo, Japan).…”
Section: Discussionmentioning
confidence: 99%
“…This information could be useful to the clinician who wants to compare CCT on a referral, where each physician has used different devices. Mo´dis et al (2001b) 570 ± 42 Bovelle et al (1999) 559.9 ± 5.5 Chakrabarti et al (2001) 538 ± 36.7 Javaloy et al (2004) 553.7 ± 25.7 McLaren et al (2004) 555 ± 28 554 ± 28 Rainer et al (2002) 541 539.2 545.1 Suzuki et al (2003) 548.1 ± 33 Tam & Rootman (2003) 550 ± 4.14 Rainer et al (2004) 544.5 ± 35.2 542.2 ± 34.3 Viestenz et al (2004) 542 ± 35 Table 3. Anterior chamber depth (ACD) using contact ultrasound biometry, as reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonik yöntemler aras›nda ultrasonik pakimetre ve ultrasonik biyomikroskop (UBM), optik yöntemler aras›nda ise speküler mikroskopi, optik koherans tomografi, taray›c› slit kornea topografisi, konfokal mikroskopi ve Pentacam Scheimpflug sistem say›labilir. 1,[7][8][9][10][11][12][13][14][15][16][17] Ultrasonik pakimetri, ucuz ve kolay uygulanabilir bir teknoloji olmas›, ölçümlerinin yüksek tekrarlanabilirlikte ve güvenilirlikte olmas› nedeniyle klinik uygulamalarda yayg›n olarak kullan›lmaktad›r. 13,[18][19][20] Korneaya temas etmesi en önemli dezavantaj›d›r ve epitel defektlerine ve enfeksiyonlara yol açabilmektedir.…”
Section: Giriflunclassified